Implementation Of Digital Marketing In Cv Aneka Sejati - Jennifer Jennifer; Dhita Hafizha Asri (Universitas Internasional Batam, 2023)
The rapid changes in various aspects that occur along with the development of time in the era of globalization in terms of running a business, encourage business people to continue to develop their business in order not to lose competitiveness with competitors. One of the ways used is digital marketing. CV Aneka Sejati, which is a supplier business where competition is very tight, has one drawback, namely that it has not implemented digital marketing which results in a lack of public attention to the marketing carried out by the company. In this study, data collection used 2 methods, namely observation and interviews to find out more clearly the problems faced by the company which took place from September 2022 to December 2022. The result of the implementation is the creation of a company Instagram account complete with content, feeds, videos and marketing posters which results in an increase in public awareness in the surrounding environment of the company as evidenced by the number of followers and likes obtained.